The Mediating Role of Social Support on Unmet Healthcare Needs in Vietnamese Older People During the COVID-19 - Long Thanh Giang PhD; Thu Dai Bui MPH; Dung Duc Le PhD; Van Thi Truong MA; Anh Lan To MPH (SAGE Publishing, 2024)
This study examined various factors, including social support as a mediating one, influencing subjective unmet needs (SUN) in Vietnamese older people during the COVID-19 pandemic. Using logistic regression models with a national survey on older persons, we identified determinants of SUN, and then further explored how social support moderated the association between experiencing SUN and chronic diseases. We found that about 25% of Vietnamese older persons experienced SUN during the pandemic, in which more advanced age, living alone, lack of healthcare insurance and having chronic diseases were risk factors, while higher education, better wealth, and stronger social support played as protective factors. Particularly, social support was found a significantly moderated factor between SUN and chronic diseases. Based on these findings, we argued that it would be imperative to strengthen healthcare system at the grassroot level so as to improve accessible and adequate care for older persons, especially those with chronic diseases. Also, enhancing social support via solidary family and community members, particularly in times of crisis, was recommended to address older persons' healthcare needs.